2007
DOI: 10.1002/ccd.20693
|View full text |Cite
|
Sign up to set email alerts
|

Intensive treatment of hypertension decreases the risk of hyperperfusion and intracerebral hemorrhage following carotid artery stenting

Abstract: Comprehensive management of arterial hypertension can lower the incidence of ICH and HPS in high-risk patients following CAS, without additional complications or prolonged hospitalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(66 citation statements)
references
References 10 publications
0
65
0
1
Order By: Relevance
“…Therefore, our data suggested that careful management of BP is required for almost 1 month after BSCAS to avoid HPS, though the incidence was relatively low. 1,21,32 Although staged CAS, because it may decrease the occurrence of HPS and HD, is more acceptable and therefore more frequently performed, there are obvious disadvantages to a staged intervention, including the higher medical cost and inconvenience to the patient. It may also potentially cause the delay of life-saving treatment such as open-heart surgery or even cause another cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our data suggested that careful management of BP is required for almost 1 month after BSCAS to avoid HPS, though the incidence was relatively low. 1,21,32 Although staged CAS, because it may decrease the occurrence of HPS and HD, is more acceptable and therefore more frequently performed, there are obvious disadvantages to a staged intervention, including the higher medical cost and inconvenience to the patient. It may also potentially cause the delay of life-saving treatment such as open-heart surgery or even cause another cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…15,25) Both CEA 8,11,13,25,28) and CAS can improve CBF impairment. 12,18,29) However, hyperperfusion syndrome (HPS) has been reported after both procedures, 1,2,10,16,17,22,23) so prevention and treatment of HPS are important issues in the perioperative management of patients undergoing CAS. Postprocedural HPS is most common in patients with CBF increases of more than 100% compared with the preoperative value, and rare in patients with CBF gains of less than 100% of the baseline value.…”
Section: Discussionmentioning
confidence: 99%
“…However, marked hemodynamic changes in the cerebral circulation associated with the reconstruction of the blood flow in the carotid artery may occur and may require intensive post-procedure management after CAS, 1,2,10,12,16,18,29) as seen in patients treated by CEA. 8,11,13,25,28) Therefore, mild hypertension to keep sufficient cerebral perfusion pressure is recommended in postoperative care for patients with preceding impaired cerebral circulation if adequate improvement in cerebral blood flow (CBF) is not observed after carotid revascularization.…”
Section: Introductionmentioning
confidence: 99%
“…14,15) However, antiplatelet agents are considered essential in CAS or for the prevention of thrombus formation at sites of stenosis. As the outcome is exacerbated by hemorrhage, even if recanalization can be achieved, we used antiplatelet agents after confirming the narrowness of the infarct area by pretreatment MRI and maintained the blood pressure low after treatment, 16) to avoid hemorrhagic complications. There has also been a report of cases in which an uneventful course without hemorrhagic complications could be obtained by performing CAS with dual-antiplatelet therapy using 100 mg aspirin and 75 mg clopidogrel following intravenous thrombolysis with rt-PA. 17) Many patients with VA or BA occlusion treated at our hospital showed satisfactory outcomes.…”
Section: Discussionmentioning
confidence: 99%